All-inclusive engagement in architecture : towards the future of social change - Ferdous, Farhana; Bell, Bryan, 1959- (London : Routledge, 2020)
Should all-inclusive engagement be the major task of architecture? All-Inclusive Engagement in Architecture: Towards the Future of Social Change presents the case that the answer is yes. Through original contributions and case studies, this volume shows that socially engaged architecture is both a theoretical construct and a professional practice navigating the global politics of poverty, charity, health, technology, neoliberal urbanism, and the discipline's exclusionary basis. The scholarly ideas and design projects of58 thought leaders demonstrate the architect's role as a revolutionary social agent. Exemplary works are included from the United States, Mexico, Canada, Africa, Asia, and Europe. This book offers a comprehensive overview and in-depth analysis of all-inclusive engagement in public interest design for instructors, students, and professionals alike, showing how this approach to architecture can bring forth a radical reformation of the profession and its relationship to society.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture and society -- Case studies; Social change -- Case studies; ARCHITECTURE / Design & Drafting